The weird, the posthuman, and the abjected world-in-itself: fidelity to the 'Lovecraft Event' in the work of Caitlín R. Kiernan and Laird Barron. Issue 6 (19th September 2017) - Jarvis, Timothy
ABSTRACT: Caitlín R. Kiernan and Laird Barron are acclaimed and influential writers of the early twenty-first century resurgence of weird fiction. But a common critical response to their writing is that they have achieved their powerful effects only by transcending the influence of the work of H. P. Lovecraft. This article argues that, while it is important to move past Lovecraft's often regressive stance, to inherit topoi from him is not necessarily to take on the more negative aspects of his personal ideology. Although his ideology was reactionary, aspects of his poetics were radical and progressive. In fact, he himself derived many of his tropes from earlier writers whose worldviews differed radically from his – the topoi were not formed by his ideology. Kiernan and Barron have used these topoi to address contemporary concerns in a progressive manner maintaining fidelity to what Benjamin Noys has called the 'Lovecraft event', while breaking with his reactionary attitudes.